A new perspective on meso-scale shoreline dynamics through data-driven analysis - Dominic Reeve (Geomorphology, 2019)
The twin ambits of climate change and coastal development have raised public awareness of shoreline management. Simultaneously, they have highlighted a gap in our understanding of sediment transport and morphodynamic processes at time and space scales appropriate for shoreline management purposes. Here, we analyse an exceptional set of beach surveys gathered over a period of twenty-two years along the Suffolk coast, eastern UK, that extends over approximately 80 km to investigate the meso-scale shoreline variations. The surveys have been made biannually along fixed transects spaced at approximately 1 km intervals as part of a strategic monitoring exercise undertaken by the coastal authorities to assist in shoreline management planning. Changes in beach volume, foreshore slope and shoreline position have been computed to investigate both spatial and temporal changes. The analysis reveals some distinct responses to the physical processes of tides and waves, anthropogenic interventions and geological controls. Neither a clear relationship between the presence of sea defences and beach response nor an ordered regional-scale shoreline movement are evident. Temporal variations in beach volumes and position provide a similarly complex picture with recessionary, accretionary and stable behaviour all apparent within the study site. There is evidence of quasi-cyclic behaviour at some locations as well as a reduction in variability over time-scales beyond approximately five years.